2015
DOI: 10.1674/0003-0031-174.2.343
|View full text |Cite
|
Sign up to set email alerts
|

An Unexpected Journey: Greater Prairie-chicken Travels Nearly 4000 km after Translocation to Iowa

Abstract: After translocation a female greater prairie-chicken (Tympanuchus cupido pinnatus) traveled over 3988 km between 5 April 2013 and 20 June 2014. The bird traveled a mean distance of 21.5 km per day during the spring (median distance per day 22.2 km; range 0-115 km per day) moving through portions of four states. Nine other marked birds traveled a mean distance of 336 km and a mean distance per day of 7.5 km during the spring (median distance per day 4.6 km; range 0-92 km per day). This is the first record of mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 13 publications
(7 reference statements)
0
7
0
Order By: Relevance
“…Greater prairie‐chickens have also been shown to exhibit exploratory movements when translocated to other areas, although the movement patterns are consistent with spiral search, not foray loops (Vogel et al. ).…”
Section: Discussionmentioning
confidence: 98%
“…Greater prairie‐chickens have also been shown to exhibit exploratory movements when translocated to other areas, although the movement patterns are consistent with spiral search, not foray loops (Vogel et al. ).…”
Section: Discussionmentioning
confidence: 98%
“…Greater sage‐grouse ( Centrocercus urophasianus ) translocations with a similar methodology to our study have shown a range of mortality (4–9%; Musil et al 1993, Baxter et al 2008, Gruber‐Hadden et al 2016) and the inability to relocate released birds (13–18.2%; Gruber‐Hadden et al 2016, Musil et al 1993, respectively) 2 to 3 weeks post release. Greater prairie‐chickens translocated to Iowa and Missouri, USA, showed similar initial mortality patterns to translocated lesser prairie‐chickens, with 24% of translocated birds dying during initial dispersal movements following release and a single bird moving >4,000 km before settling (Kemink and Kesler 2013, Vogel et al 2015). Similarly, 13% of translocated greater prairie‐chickens in Missouri were not found after release (Carrlson et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Frith (1962a) reported that most Malleefowl struggle to colonize new areas when their habitat is heavily cleared and perish. Seasonal movements and (predominantly female) long‐range dispersal in other medium‐sized ground‐dwelling birds that live in similarly fragmented habitats highlight the importance of dispersal in population connectivity and resulting gene flow (Earl et al, 2016; Vogel, 2015).…”
Section: Discussionmentioning
confidence: 99%